Revitalizing Ijtihād and Ittibāʾ in Abdul Hamid Hakim’s Works: A Study of Intellectual Reforms Within Islamic Legal Theory - Fanani, Ahwan; Baroroh, Umul; Hamzani, Achmad Irwan (Fakultas Agama Islam, Universitas Muhammadiyah Yogyakarta, 2024)
Uṣūl fiqh played an important role in the discussion of fiqh, but it is no longer applied for legal deduction due to the prevalent idea of taqlīd (imitation). The taqlīd hinders Islamic the scholars from referring to the Quran and sunnah directly. Abdul Hamid Hakim's efforts to revitalize ijtihād (independent reasoning) and ittibāʾ (evidence based accaptance) have brought new nuances to uṣūl fiqh. This paper aims to describe the thoughts of ijtihād and ittibāʾ in the works of Hakim and to reveal the influence of Islamic renewal. This paper is based on literature research using qualitative methods with a historical approach. This research shows that the uṣūl fiqh works of Hakim are written with an applicative approach. He arranges his works as teaching materials for beginners to advanced students. The idea of revitalizing ijtihād and encouraging ittibāʾ in Hakim’s works resonated Islamic renewal idea in the early 20th century, marked by the creed of returning to the Quran and sunnah and the opening the ijtihād door. Hakim’s works have contributed to the development of Islamic legal thought in Indonesia, which influenced subsequent efforts to reform Islamic law in the country.